Pengaruh Viral Marketing Instagram Dan Celebrity Endoser Terhadap Minat Beli Produk Scarlet Whitening Pada Masyarakat Kecamatan Jagakarsa - Aqilah, Yoni Adani; Prehantio, Tri Waluyo (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aimed to find out and analyze the influence of Instagram viral marketing and celebrity endorsers on the interest in purchasing Scarlett Whitening products among the people of Jagakarsa Subdistrict. The research method used descriptive analysis with a quantitative approach. The population of this research was the population of Jagakarsa Subdistrict, with sampling using the Hair formula, resulting in a sample of 100 respondents. The data analysis technique in this research used descriptive statistics with multiple linear regression analysis. Each respondent was given 30 statements using a Likert scale, and this research used instrument testing (validity and reliability tests), classical assumption tests (normality, multicollinearity, and heteroscedasticity tests), multiple linear regression analysis, hypothesis testing (T-test, F-test, and coefficient of determination), and f- test. Meanwhile, data processing used the SPSS version 26 for Mac program. The results showed that viral marketing and celebrity endorsers had a significant simultaneous influence on purchase interest. The coefficient of determination (R2) showed that the viral marketing and celebrity endorser variables had a simultaneous influence of 13% on purchase interest, while the remaining 87% was influenced by other variables not researched in this research.